The Correlation between Students' Problem-Solving Abilities and Their Mathematical Thinking in High School Mathematics Education - Firmansyah, Edwar; Baluta, Ines Buissa; Elfaituri, Khaled (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The aim of this study is to explore the relationship between students' problem-solving abilities and mathematical thinking, and to identify how these two abilities can support each other in the development of holistic mathematical skills in secondary education. Methodology: This study uses quantitative methods with correlational and survey designs. The instrument used is a written test, consisting of story questions and multiple choices. Data collection is done through structured observation and documentation. The software used for data analysis is SPSS, with descriptive and inferential statistical analysis techniques, including the Pearson correlation test and simple linear regression test. Main Findings: The results of the study showed that there was a strong and significant relationship between problem-solving ability and mathematical thinking of students in grades 11.F1 (r = 0.74, p = 0.001) and 11.F3 (r = 0.68, p = 0.003). Problem-solving ability was also shown to predict mathematical thinking with a significant effect (R² = 0.55, p = 0.001). The problem-solving factor can explain 55% of the variance in students' mathematical thinking. Novelty/Originality of this study: This study shows a strong correlation between secondary school pupils' mathematical thinking and problem-solving skills, particularly when it comes to number-related content. The study's originality is the finding that students' problem-solving skills can anticipate how their mathematical thinking will evolve, offering fresh perspectives for creating learning models that would simultaneously improve both abilities.